Improvements In Asthma Outcomes By Community Pharmacist Interventions: Do They Last? - Armour, C.; Saini, B.; Bosnic-Anticevich, S.; Krass, I.; LeMay, K.; Alles, C.; Burton, D.; Stewart, K.; Emmerton, Lynne; Reddel, H. (Stanford University, 2011)
Asthma management in primary care is less than optimal. We investigated the feasibility and outcomes associated with the introduction of a specialised asthma management service conducted by trained community pharmacists. Pharmacists were selected for inclusion based on structural requirements in the pharmacy (e.g. a separate room for counselling) and their location, so that a representative sample of urban and rural pharmacies from 3 Australian states and 1 territory were included. Ninety-six community pharmacists recruited 570 patients with sub-optimally controlled asthma and/or no recent asthma review. A complex and structured intervention was conducted over 6 months and asthma outcomes measured. The intervention included lung function assessment and review of asthma control, patient education on trigger factors, medication use and adherence, inhaler technique as well as goal setting to support patient self management. Outcomes were measured at the end of the intervention (6 months) and at 12 months, where a subset of patients (n=144) received a follow-up visit, and then at 18 months.Significant improvements in asthma control, quality of life, inhaler technique, adherence to regimen, perceived control and asthma knowledge were observed at the end of the 6-month intervention. Fewer patients were reliant on short-acting beta agonists alone, and significantly more used combination controller inhalers. These positive health outcomes were associated with high levels of satisfaction both from the patient and pharmacist perspective. At 12 months, the improved outcomes were sustained in the subset of patients who received a follow up visit , but there was a small deterioration in asthma control in the patients who did not receive a follow-up visit. At 18 months there was a significant deterioration in asthma control. Community pharmacists can have a positive impact on the health of people with asthma and this is sustained for 6 months; there may need to be further review at 6 or 12months post-intervention for the health benefits to be sustained.